2019
DOI: 10.1016/j.injury.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Choice of three different intramedullary nails in the treatment of trochanteric fractures: Outcome, analysis and consideration in midterm

Abstract: The purpose of this study is to compare the results obtained using three different systems of osteosynthesis, developed for the surgical treatment of fractures of the trochanteric region of the femur, based on the principle intramedullary nailing: the Gamma nail, the Affixus nail and the ZNN nail. This is a retrospective study: 72 trochanteric fractures treated with the Gamma nail, 68 treated with the Affixus nail and 69 treated with the ZNN nail, between the years 2012 and 2014, with the prerequisite of a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Only two patients had an arterial injury requiring intervention (in one patient the responsible branch was ligated intra-operatively and in the other embolised pre-operatively), whilst the remaining patients had 54%; open reduction group: 69%) revealed a smaller proportion of subtrochanteric femur fractures requiring blood transfusion. 26,27 Noteworthy, the number of units RBC required (mean: 1.4-1.7 units dependant on implant choice) by patients with intertrochanteric fractures was lesser than those with subtrochanteric fractures, as observed by both our study and Shukla et al 26,27 Taken altogether, the higher incidence for blood transfusion as observed in subtrochanteric fractures could be explained by the greater proportion of these patients being elderly fragility fractures, often with a lower biological reserve of baseline Hb. 23 In their regression analysis, Wertheimer et al examined the risk factors for blood transfusion in the first 48 h. 23 They identified admission Hb as the only statistically risk factor determining the need for blood transfusion (p < 0.01), with only a trend observed for male gender (p = 0.08).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Only two patients had an arterial injury requiring intervention (in one patient the responsible branch was ligated intra-operatively and in the other embolised pre-operatively), whilst the remaining patients had 54%; open reduction group: 69%) revealed a smaller proportion of subtrochanteric femur fractures requiring blood transfusion. 26,27 Noteworthy, the number of units RBC required (mean: 1.4-1.7 units dependant on implant choice) by patients with intertrochanteric fractures was lesser than those with subtrochanteric fractures, as observed by both our study and Shukla et al 26,27 Taken altogether, the higher incidence for blood transfusion as observed in subtrochanteric fractures could be explained by the greater proportion of these patients being elderly fragility fractures, often with a lower biological reserve of baseline Hb. 23 In their regression analysis, Wertheimer et al examined the risk factors for blood transfusion in the first 48 h. 23 They identified admission Hb as the only statistically risk factor determining the need for blood transfusion (p < 0.01), with only a trend observed for male gender (p = 0.08).…”
Section: Discussionsupporting
confidence: 62%
“…Comparing the blood loss between femoral diaphyseal fractures and that of ‘extremity’ fractures (70.3% being subtrochanteric fractures), Wertheimer et al reported a higher incidence of blood transfusion (within first 48 h and overall total transfusion requirement) in patients with ‘extremity fractures’. Interestingly, when compared against intertrochanteric femoral fractures (95.8%), findings from both our study (overall: 62.7%) and Shukla et al (closed reduction group: 54%; open reduction group: 69%) revealed a smaller proportion of subtrochanteric femur fractures requiring blood transfusion 26,27 . Noteworthy, the number of units RBC required (mean: 1.4–1.7 units dependant on implant choice) by patients with intertrochanteric fractures was lesser than those with subtrochanteric fractures, as observed by both our study and Shukla et al 26,27 Taken altogether, the higher incidence for blood transfusion as observed in subtrochanteric fractures could be explained by the greater proportion of these patients being elderly fragility fractures, often with a lower biological reserve of baseline Hb 23 …”
Section: Discussionsupporting
confidence: 40%
“…Subtrochanteric fractures have been widely reported to run a high risk of developing implant-related complications and fracture non-union [ 23 , 24 , 25 ], and most importantly high rates of re-operation [ 26 , 27 , 28 , 29 ]. However, despite SSI being such a common complication, published studies on subtrochanteric focus were mainly focused on outcomes in terms of fracture healing and survivorship [ 23 , 24 , 25 , 26 ]. As such, knowledge surrounding the incidence, associations, pathogenic micro-organisms and the management outcomes of SSIs in surgically treated subtrochanteric fracture remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical time (Gamma nail: 104.1 min; Affixus nail: 114.5 min) and length of stay (Gamma nail: 23.7 days; Affixus nail: 23.6 days) were comparable between the two nails in our study group. This finding is similar to that of Persiani et al, who, to our knowledge, performed the only study that compared the use of Affixus and Gamma nails in the treatment of trochanteric fractures [ 26 ]. Mortality rates at 1 year were not significantly different between the two nail groups.…”
Section: Discussionmentioning
confidence: 88%